Reconceptualizing Teacher Readiness for Deep Learning: Challenges and Adaptive Practices in Islamic Religious Education - Wini Afriani; Rahmi Wiza (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to reconceptualize teacher readiness for deep learning by examining the challenges faced by Islamic Religious Education teachers and the adaptive practices they employ during the implementation of deep learning within the Merdeka Curriculum. Although deep learning has been widely promoted as an innovative pedagogical approach capable of fostering meaningful understanding, critical thinking, reflection, and character development, its successful implementation remains highly dependent on teachers’ readiness to translate its principles into classroom practice. This study adopted a qualitative descriptive design and was conducted at SMA Negeri 1 Sutera, Pesisir Selatan Regency, Indonesia, from May to June 2026. Data were collected through participatory classroom observations, semi-structured interviews, and document analysis involving two Islamic Religious Education teachers, one vice principal for curriculum affairs, and eight Grade XI students selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was established through source and method triangulation. The findings indicate that the implementation of deep learning is constrained by both internal and external factors. Internal challenges include limited conceptual understanding of mindful, meaningful, and joyful learning, difficulties in designing deep learning-oriented instruction, uneven pedagogical content transformation, and limited integration of educational technology. External challenges involve infrastructural limitations, restricted instructional time, and diverse student characteristics. Despite these challenges, teachers demonstrated adaptive practices through continuous professional learning, instructional adjustments, gradual technology utilization, and reflective evaluation. The novelty of this study lies in its reconceptualization of teacher readiness as a dynamic and multidimensional construct encompassing conceptual, pedagogical, technological, reflective, and institutional dimensions. This study contributes to the literature by extending current understandings of deep learning implementation in Islamic Religious Education and providing an empirically grounded framework for strengthening teacher readiness and pedagogical transformation in religious education contexts.